Pedagogical Anchors Amid Pedagogical Dilemmas: The Myth of Innovation and Unsustainable Expectations within Mathematics Education Research - Surur, Agus Miftakus; Pujilestari, Sri; Ridwanulloh, M. Ubaidillah (International Journal of Review in Mathematics Education, 2026)
Frequent curriculum changes disrupt instructional rhythms and stigmatize lecture methods, creating "unrealistic" situations within mathematics education research. Current trends demand total innovation, such as PBL or PjBL across all chapters, which is logistically impossible without sacrificing curriculum completion. This study aims to conceptualize the "pedagogical anchor" as a rational and professional response to maintain instructional stability. Employing a critical literature review of previous theses and dissertations, the research compares preparation-to-coverage ratios between experimental settings and real-classroom demands. Findings reveal a significant scale anomaly where "successful" innovations are often limited to single chapters and lack long-term sustainability due to workload mismatches. The study concludes that strategic lecturing serves as a necessary anchor for cognitive stability rather than an anti-innovation stance. It recommends a shift toward an integrated longitudinal research model that supports teachers throughout the academic year. This approach is essential to prevent collective fatigue and ensure meaningful, sustainable educational innovation.